PERKEMBANGAN PEMEROLEHAN BAHASA DAN ALAT-ALAT TUBUH YANG BERPERAN DALAM PEMEROLEHAN BAHASA - Gress Vinessa Simorangkir; Septian Alya Hustria; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The acquisition of language is a crucial process in human cognitive and social development. This article discusses the stages of language acquisition in children and the bodily tools that support this process, such as the brain, nervous system, and speech apparatus. The research includes a theoretical analysis from linguistic and neurobiological perspectives and explores the roles of the brain and articulatory organs in language acquisition. Various theories from recent experts, including studies from the last five years, are employed to review the role of each bodily tool in supporting language acquisition. Through a literature approach and empirical research, this article reveals the interaction between biological development and social environment in the language acquisition process. The conclusion drawn is that language acquisition results from a complex interaction between inherent biological abilities and environmental stimulation, particularly social interactions